The profile of patients’ complaints in a tertiary care hospital in South India - Nalakath, Mohammed Jezeel; Thasneem, P. M.; Deepak, K. V.; Uvais, N. A. (International Journal Of Community Medicine And Public Health, 2018)
Background: Complaints from patients and their carers are important indicators of problems in a healthcare system and provide valuable insights into safety-related problems within healthcare organisations. The objectives of the present study are to identify the frequency distribution of the people complained about, the units complained about and the total number of complaints. Methods: We employed a descriptive, cross-sectional study to conduct this research. The research population included cases registered at the complaints unit of a tertiary care hospitals in selected months of May 2017 to August 2017. The data were collected through observation of available documents. Excel software program was used for data analysis. Results: The administration received 692 complaints between the study period. The highest rate of complaints was filed against admission process (30.06%) and the lowest rate of complaints are filed against staff (2.51%). Our study results showed a significantly less complaints against nursing staff and no complaints against medical staff, indicates that the nursing and medical staff of the hospital might be observing medical ethics and professional commitment to a high standard and communicating well with the patients. High rate of complaints against admission unit, house keeping unit and high billing amount indicates the unrealistic expectations prevailing in the minds of clients from the health care provider. Conclusions: The current study generated the profile of patient’s complaints in a tertiary care hospital running in a charitable model. Such data can be utilised to identify common problems and to plan strategies.